PDF profiling using the forward-backward asymmetry in Neutral Current Drell-Yan production - Elena Accomando; Juri Fiaschi; Francesco Hautmann; Stefano Moretti; the xFitter Developers’ team: Hamed Abdolmaleki; Valerio Bertone; Francesco Giuli; Alexander Glazov; Agnieszka Luszczak; Ivan Novikov; Fred Olness; Oleksandr Zenaiev (Journal of High Energy Physics, 2019)
Abstract Non-perturbative QCD effects from Parton Distribution Functions (PDFs) may be constrained by using high-statistics Large Hadron Collider (LHC) data. Drell-Yan (DY) measurements in the Charged Current (CC) case provide one of the primary means to do this, in the form of the lepton charge asymmetry. We investigate here the impact of measurements in Neutral Current (NC) DY data mapped onto the Forward-Backward Asymmetry (A FB) on PDF determinations, by using the open source fit platform xFitter. We demonstrate the potential impact of A FB data on PDF determinations and perform a thorough analysis of related uncertainties.